THE EFFECT OF SOCIAL MEDIA MARKETING, BRAND IMAGE AND RELIGUSITY ON THE PURCHASE DECISION OF BALI TRADITIONAL CLOTHING (STUDY ON VISITORS AND FOLLOWING INSTAGRAM LAKSMI_KEBAYABALI ACCOUNTS IN BANDAR LAMPUNG): PENGARUH SOCIAL MEDIA MARKETING, BRAND IMAGE DAN RELIGIUSITAS TERHADAP KEPUTUSAN PEMBELIAN BUSANA ADAT BALI (STUDI PADA PENGUNJUNG DAN PENGIKUT AKUN INSTAGRAM LAKSMI_KEBAYABALI) DI BANDAR LAMPUNG) - Pratama, Wayan Agus; Djausal, Gita Paramita (Jurnal Kompetitif Bisnis, 2023)
Social media marketing is a form of online advertising that uses the cultural context of social communities including social networks, virtual worlds, social news sites, and social opinion sharing sites to meet communication goals. Social media marketing carried out by a business can influence a person’s thinking which will have an impact on the thoughts of others more broadly before making a purchase decision. The demand for increasingly quality products makes companies engaged in their fields to improve the quality of their products to improve the brand image of their products, so that consumers make their religiosity a guide for making purchasing decisions. The research conducted is the influence of social media marketing, brand image and religiosity on the decision to buy Balinese traditional clothing (study of visitors and followers of the Laksmi_Kebayabali Instagram account in Bandar Lampung) with the aim of knowing the effect of social media marketing, brand image, and religiosity on decisions. purchase of Balinese traditional clothing at Laksmi Kebaya. The type of research used is explanatory research with a quantitative approach. The population in this study were followers and visitors of Laksmi Kebaya Instagram in Bandar Lampung. Sampling technique using accidental sampling with a sample of 100 respondents. The data was obtained from a questionnaire using a Likert scale. The results of the partial test show that the three dependent variables, namely social media marketing, brand image and religiosity, have an effect on purchasing decisions for Balinese traditional clothing on Instagram Laksmi_kebayabali. Simultaneously shows that social media marketing, brand image and religiosity affect the purchasing decision of Balinese traditional clothing on Instagram Laksmi_kebayabali with a medium value, which is 51.9%. Keywords: Social media marketing, Brand Image, Religiosity and Purchase decision.